Partial or Truncated Sharing Values of Meromorphic Functions with Their Shifts (Communications in Mathematical Research, 2019)
We mainly study the periodicity theorems of meromorphic functions havingtruncated or partial sharing values with their shifts, where meromorphic functionsare of hyper order less than 1 and $N(r,\,f)=α T(r,\,f)$ for some positive number $α$.
Keywords: meromorphic function; periodicity; truncated sharing value; partial sharing value